COMPARISON BETWEEN THE CRIME OF FRAUD AND THE CRIMES OF FORGERY - Alexandru STAN (Challenges of the Knowledge Society, 2025)
This article aims to analyze and comparatively comment on the crimes of fraud and forgery in the Romanian Criminal Code from theory and from older and more recent judicial practice. As can be seen from the examples cited in this paper, there are numerous contradictory solutions and controversial aspects relative to the analyzed crimes, which have not disappeared with the advent of the new Criminal Code of 2014. For this reason, we believe that this paper can be useful for both theorists and practitioners, and the purpose of this material is not only the presentation and comparative analysis of the crimes of fraud and forgery, but also the proposal of solutions that, even if they will not be embraced by theorists and practitioners of criminal law, can at least constitute a basis for discussion for the unitary application of criminal law. Even if we cannot exhaust the subject through this work, we believe that we have reached the essential points that can generate controversy and debate, and depending on the opinions that will be expressed later on the issues addressed, we will return with a more complex work, which will also take into account the other points of view of criminal law specialists or practitioners.